2017
DOI: 10.5194/tc-11-2363-2017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the local-scale influence of sea ice on Greenland surface melt

Abstract: Abstract. Rapid decline in Arctic sea ice cover in the 21st century may have wide-reaching effects on the Arctic climate system, including the Greenland ice sheet mass balance. Here, we investigate whether local changes in sea ice around the Greenland ice sheet have had an impact on Greenland surface melt. Specifically, we investigate the relationship between sea ice concentration, the timing of melt onset and open-water fraction surrounding Greenland with ice sheet surface melt using a combination of remote s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 78 publications
4
30
0
Order By: Relevance
“…A wide range of approaches have previously indicated that Baffin Bay sea ice changes impact conditions on Greenland. Rennermalm et al () and Stroeve et al () present process‐based analyses linking sea ice loss through changed surface fluxes to increased melt on GrIS. In agreement with the signals we see along the west coast (Figure ), both of these studies find that sea ice loss in Baffin Bay promotes melting on the adjacent parts of the ice sheet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of approaches have previously indicated that Baffin Bay sea ice changes impact conditions on Greenland. Rennermalm et al () and Stroeve et al () present process‐based analyses linking sea ice loss through changed surface fluxes to increased melt on GrIS. In agreement with the signals we see along the west coast (Figure ), both of these studies find that sea ice loss in Baffin Bay promotes melting on the adjacent parts of the ice sheet.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term view employed here is inspired by detection and attribution studies used, for example, in the context of the Intergovernmental Panel on Climate Change (Bindoff et al, 2013). It is meant to supplement process-based analyses (e.g., Rennermalm et al, 2009;Stroeve et al, 2017), attempting to reveal covariability between changes in different parts of Greenland and the state of the sea ice cover and the state of the global climate, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summer, the polar vortex is slightly weaker in CESM2, with its central geopotential height overestimated by 2 dams (Figure f), although the southward expansion of the polar vortex appears exaggerated. September sea ice extent is slightly underestimated in CESM2 (Figure e), but there is good agreement near Greenland, suggesting that substantial GrIS SMB biases due to sea ice biases are unlikely (Noël et al, ; Stroeve et al, ).…”
Section: Resultsmentioning
confidence: 95%
“…For example, sea ice loss is projected to continue, including periods of especially rapid change (e.g., Holland et al, 2006; rapid declines already occurred in 2007 and 2012; Stroeve et al, 2012). Rapid sea ice loss not only heightens atmospheric warming, but also early loss of sea ice locally near the Greenland Ice Sheet may increase heat transfer from the ocean to the atmosphere above the ice sheet and result in increased ice sheet melt (Stroeve et al, 2017). Rapid sea ice loss also has a significant effect on temperatures over land with implications for permafrost thaw (Lawrence et al, 2008), and increased wave activity due to sea ice loss can also lead to stronger permafrost coastal erosion, further exacerbated by sea level rise from land ice loss (Fritz et al, 2017).…”
Section: Connections Across the Arctic Systemmentioning
confidence: 99%